2020
DOI: 10.1016/j.renene.2020.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels beads for cooling solar panels: Experimental study

Abstract: This paper aims to present a new and novel experimental study for the usage of hydrogel beads with different bed configurations as a cooling attachment underneath solar panel. Four different bed configurations were studied using different layers and fins arrangements then compared with the un-cooled system. The best results were obtained using 3 rows of hydrogel beads with fins where the panel temperature dropped by approximately 10 ̊ C below the uncooled panel at 1000 W/m 2 (representing around 14% temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The experiment setup used in this study is similar to the setup in [18]. Experiments are done under two radiation intensities of 1000 W/m 2 and 800 W/m 2 to simulate the highest and medium solar intensities reaching the earth surface as reported in [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment setup used in this study is similar to the setup in [18]. Experiments are done under two radiation intensities of 1000 W/m 2 and 800 W/m 2 to simulate the highest and medium solar intensities reaching the earth surface as reported in [20].…”
Section: Methodsmentioning
confidence: 99%
“…The containers for the three rows of nano saturated hydrogels were manufactured from Acrylic with rectangular slot perforation to allow for maximum air circulation. These number of rows were optimised for cooling solar panels earlier in [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdo et al investigated the cooling performance of hydrogel beads in photovoltaic panels and the working temperature can be reduced by ≈10 K, resulting in a relative PCE increase of 7.2%, compared to that of c‐Si photovoltaic panels. [ 154 ] Additionally, Dida et al employed the burlap cloth to directly attach the rear surface of photovoltaic panels, which can enable a temperature drop of ≈20 K, corresponding to a relative PCE increase of 14.75%. [ 155 ] Moreover, Lv et al proposed the coupling of evaporative cooling with phase change materials, which can theoretically enhance the cooling performance of photovoltaic panels.…”
Section: Passive Evaporative Coolingmentioning
confidence: 99%
“…This composite hydrogel could dissipate considerable amount of latent heat thermal energy. Abdo et al 25 used saturated hydrogel for solar panel cooling in their solar simulator experiment. They observed that the temperature of solar panels drop by 9 and 9.6 ℃ at 600 and 1000 W/m² radiation.…”
Section: Introductionmentioning
confidence: 99%